The N170 Shows Differential Repetition Effects for Faces, Objects, and Orthographic Stimuli - Mercure, Evelyne; Cohen Kadosh, Kathrin; Johnson, Mark (Frontiers in Human Neuroscience, 2011)
Previous event-related potentials (ERPs) research has suggested that the N170 component has a larger amplitude to faces and words than to other stimuli, but it remains unclear whether it indexes the same cognitive processes for faces and for words. The present study investigated how category-level repetition suppression effects on the N170 differ across stimulus categories. Faces, cars, words and non-words were presented in homogeneous (1 category) or mixed blocks (2 intermixed categories). We found a significant repetition suppression effect of N170 amplitude for successively presented faces and cars (in homogeneous blocks), but not for words and unpronounceable consonant strings, suggesting that the N170 indexes different underlying cognitive processes for objects (including faces) and orthographic stimuli. The N170 amplitude was significantly smaller when multiple faces or multiple cars were presented in a row than when these stimuli were preceded by a stimulus of a different category. Moreover, the large N170 repetition suppression effect for faces may be important to consider when comparing the relative N170 amplitude for different stimulus categories. Indeed, a larger N170 deflection for faces than for other stimulus categories was observed only when stimuli were preceded by a stimulus of a different category (in mixed blocks), suggesting that an enhanced N170 to faces may be more reliably observed when faces are presented within the context of some non-face stimuli.